Dinuclear copper(II) complexes as testing ground for molecular magnetism theory. (1st September 2019) - Castro, Isabel; Calatayud, María Luisa; Yuste, Consuelo; Castellano, María; Ruiz-García, Rafael; Cano, Joan; Faus, Juan; Verdaguer, Michel; Lloret, Francesc
Graphical abstract: A long journey of molecular magnetism is briefly reviewed covering almost fifty years of work on the use of dicopper(II) complexes as experimental and theoretical models for the study of the through-ligand magnetic coupling phenomenon. Abstract: A leitmotiv in the field of molecular magnetism is the study of the electron exchange (EE) magnetic interactions among distant metal centers through the corresponding bridging ligands in polynuclear coordination compounds. The present review provides a historical perspective on the use of dinuclear copper(II) complexes with either simple inorganic or extended organic bridging ligands as experimental and theoretical models for the fundamental research on the relative importance of the spin delocalization and spin polarization mechanisms of the EE interaction across σ- and π-type orbital pathways. Particular focus is placed on the work by Professor Miguel Julve, outstanding researcher and an excellent teacher, best friend and colleague, in recognition of his invaluable contributions to molecular magnetism on the occasion of his 65th anniversary.